2015
DOI: 10.1016/j.hlc.2015.06.683
|View full text |Cite
|
Sign up to set email alerts
|

The Cardiac Genetics Clinic – a model for multidisciplinary genomic medicine

Abstract: 679Sudden cardiac death from genetic heart disease: psychological impact to the surviving at-risk family members

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…The uptake of gene panel tests has been rapid and included a volume of successful direct-to-the-public marketing. In some areas of clinical genetics, panel testing is now the standard of care [ 1 ]. With some important caveats and considerations discussed in this review, current data suggests that gene panel testing offers breast cancer clinical genetics practice increased opportunity to identify “actionable” genetic variants in a greater proportion of women [ 2 – 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The uptake of gene panel tests has been rapid and included a volume of successful direct-to-the-public marketing. In some areas of clinical genetics, panel testing is now the standard of care [ 1 ]. With some important caveats and considerations discussed in this review, current data suggests that gene panel testing offers breast cancer clinical genetics practice increased opportunity to identify “actionable” genetic variants in a greater proportion of women [ 2 – 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Developments in genomic science are disproportionately in advance of their translational clinical application. Multidisciplinary clinics are proposed to overcome this 1 in many medical fields 2 . This is especially so in nephrology, which is typified by significant community disease burden 3 and heritability 4 .…”
mentioning
confidence: 99%
“…Thirty‐six potentially relevant papers were identified and read in full‐text (Figure 1). Only six peer‐reviewed papers (Bradley & Bowdin, 2016; Strider et al, 1996; Summers et al, 2006; von Kodolitsch et al, 2016; Wright et al, 2016; Zentner et al, 2015) and two conference abstracts (Andvik et al, 2011; McLean, 2012) met the eligibility criteria and were included in this review (Table 1). Excluded articles with reasons for exclusion are presented in Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…Excluded articles with reasons for exclusion are presented in Table S1. The included peer‐reviewed papers comprised a prospective study (Strider et al, 1996), one case series (Summers et al, 2006), one retrospective chart review (Zentner et al, 2015), one innovation report (Wright et al, 2016) and two narrative reviews/ expert experiences (Bradley & Bowdin, 2016; von Kodolitsch et al, 2016). Four studies (Andvik et al, 2011; Strider et al, 1996; Summers et al, 2006; Zentner et al, 2015) reported patient data on a total of 771 patients with MFS and other HTADs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation